Electrochemical Extraction of Praseodymium From LiCl-KCl Molten Salt System on Liquid Zn Cathode - JI De-bin; LIU Yao; WANG Pu; QIAO Zhi-qiang; YAN Yong-de; ZHANG Mi-lin; WU Hong-jun (He huaxue yu fangshe huaxue, 2023)
Many researchers have carried out studies on the electrochemical separation and extraction of rare earth and actinide elements at different cathodes by molten salt electrolysis method, aiming at the application in the reprocessing of spent fuel. Using liquid metal as cathode has many advantages. In recent years, literatures on the topic of electrochemical separation and extraction of rare earth elements in molten salt system mainly used liquid Bi, Al, Mg, Pb and Ga as cathode. Compared with above liquid metal cathode, liquid Zn cathode is easy to form alloy with rare earth elements, and has high separation and extraction efficiency. In addition, rare earth elements are the main fission products in spent fuel, and their chemical properties are highly similar to actinides. It is difficult to realize the separation of rare earth elements from actinide elements. As a consequence, it is significant to study the electrochemical behavior of rare earth ions on liquid Zn cathode in the molten salt system. In this study, cyclic voltammetry and semi-integral method were employed to investigate the electrochemical reduction processes of Pr(Ⅲ) on the W electrodes and liquid Zn electrodes in LiCl-KCl-PrCl3 molten salts at 773 K. The diffusion coefficients of Pr(Ⅲ) in LiCl-KCl molten salts were measured and calculated through cyclic voltammetry and semi-differential method at 773 K. Electrochemical extraction of Pr was implemented on liquid Zn cathode at 773 K in LiCl-KCl melts by potentiostatic electrolysis, and the extraction efficiency was evaluated with the assistance of ICP analysis. The obtained deposit was analyzed by the X-ray diffraction(XRD) and scanning electron microscopy(SEM) equipped with energy dispersive spectrometry(EDS). After potentiostatic electrolysis for 2 h, the extraction efficiency is 45.38%. When the electrolysis time reaches 40 h, the extraction efficiency is 99.48%. XRD and EDS quantitative analysis illustrates that the obtained deposit mainly contains Zn11Pr3 phase after potentiostatic electrolysis for 2 h.